POLA MAKAN, ASUPAN ZAT GIZI, DAN STATUS GIZI ANAK BALITA BAWAH GARIS MERAH DI PESISIR PANTAI DESA TATENGESAN DAN MAKALU WILAYAH KERJA PUSKESMAS PUSOMAEN - Rivolta G.M. Walalangi; Olfie Sahelangi; Gita Widodo (POLTEKKES KEMENKES MANADO, 2015)
Toddler group is showing rapid growth of the body, so it requires nutrients that every high Kgweight. Children this age group it is most often suffer from a lack of nutrition CTF. Based onthe data reports Pusomaen PHC in November 2014, the number of infants were detectedbelow the red line (BGM) of 20 children (8.62%).The study was observational and descriptive in order to determine the diet, nutrient intake andnutritional status of children under five (BGM) in the coastal village Tatengesan and Makalu.The research was conducted in May in the health Pusomaen the number of samples 15children. Diet using FFQ and nutrient intake using a food recall 2x24 hours.The results showed consumption of rice to eat (86.7%), fish and eggs (66.7%), out (66.7%),green vegetables (13.3%), bananas (46.7%). For rice mixed with salt and palm oil and sugaras a drink, often consumed. Frequency of eating 3 times a day with the type or sususnan mealconsists of a staple food such as rice, fish, vegetables and fruit. On average nutrient intake ofchildren below the red line (BGM) is: 633.7 kcal of energy, protein 21.05 grams, 18 grams offat and carbohydrate grams 112.55. These results indicate a lack of nutrient intake in childrenunder five.